Impact of host switching at different larval instars on the performance of the polyphagous pest Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) - Baran Aslan; Ali Kemal Birgücü; Ebru Gül Aslan (Scientific Reports)
Abstract Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) is a highly adaptable and destructive pest of tomato crops, posing a significant threat to global agriculture due to its rapid spread and resistance to control measures. This study investigates the developmental rates and population parameters of T. absoluta larvae when transferred between three host plants—tomato, eggplant, and tobacco—across four distinct larval instars. Larvae were reared under controlled environmental conditions (25 ± 1 °C, 60 ± 5% RH, and 16L:8D photoperiod) and transferred between these hosts at the first to fourth instars. Life table analyses, including parameters such as net reproductive rate (R₀) and intrinsic rate of increase (r), were used to evaluate developmental times, survival, and reproductive potential across different hosts. The results showed that T. absoluta could complete its life cycle on all three host plants, although tobacco significantly prolonged the developmental periods, likely due to its high nicotine content, making it a less suitable host. In contrast, tomato supported the most optimal development, while third-instar larvae transferred to eggplant exhibited higher performance than those reared solely on tomato. These findings suggest that T. absoluta shows increased adaptability to eggplant at later developmental stages. The study highlights the pest’s ability to exploit different hosts, particularly from the third instar onward, and underscores the importance of host selection in shaping pest management strategies. The results have implications for integrated pest management (IPM) approaches, emphasizing targeted interventions based on host plant suitability and developmental stage.